Clinical Presentation and Management of Emergency Patients with Epistaxis in Babylon Governorate - Aboud, Haneen Riyadh; AL-Turaihy, Safaa (American Journal of Biomedicine and Pharmacy, 2026)
Background: Epistaxis, commonly known as nosebleeds, is a frequent cause of emergency visits, affecting individuals of all ages. It is particularly prevalent among populations exposed to specific environmental triggers, such as dry air, which is common in the Babylon Governorate of Iraq. The condition can range from mild, self-limiting bleeding to severe episodes that cause significant discomfort and even hemodynamic instability. Despite its common occurrence, the management of epistaxis remains a clinical challenge, especially in resource-limited settings. Previous studies have identified various etiological factors contributing to epistaxis, including environmental conditions, trauma, and underlying health conditions such as hypertension. However, there is limited data on the clinical presentation and management strategies for epistaxis in the emergency departments (ED) of regional hospitals in Iraq, making it crucial to gather insights into the effectiveness of different treatment modalities in such settings. Methods: A cross-sectional study was conducted involving 60 patients who presented with epistaxis at three major hospitals: Al-Hilla Teaching Hospital, Merjan Teaching Hospital, and Imam Al-Sadiq Teaching Hospital. The data collection process included gathering demographic information, clinical history of epistaxis, and the treatment methods administered during the emergency visit. Results: The analysis of patient demographics revealed a male predominance, with 40 males (67%) and 20 females (33%) in the study sample. The age distribution indicated that the highest number of cases occurred in the 11–20 years age group (27.5%), followed by the 21–29 years group (25%). The mean age for male patients was 23.80 ± 13.55 years, while for females it was 35.30 ± 24.46 years, with a statistically significant difference between the genders (p = 0.022). Regarding etiological factors, dry air was the most common trigger for epistaxis, affecting 38% (n=23) of patients, followed by nasal trauma at 25% (n=15), and sneezing at 23% (n=14). Other less frequent causes included the use of anticoagulants (8%) and nose scratching (5%). A higher prevalence of dry air and nasal trauma was observed in younger male patients, particularly within the 11–29 age group. Management strategies showed that conservative interventions, such as manual pressure, were the most commonly used treatment, applied in 62% (n=37) of cases. Anterior nasal packing (ANP) (10%) and intravenous tranexamic acid (IV TXA ) (8%) were used in more severe cases, while posterior nasal packing ( PNP ) (3%) was employed the least. The results emphasize that conservative treatments are highly effective for managing epistaxis, with a minimal need for invasive procedures. Conclusion:This study offers valuable insights into the clinical characteristics and management of epistaxis in Babylon, Iraq. Dry air was identified as a major environmental factor contributing to the condition, emphasizing the importance of public awareness and preventive measures, such as nasal hydration. Conservative management, particularly manual pressure, was found to be the most effective first-line treatment for epistaxis in this setting. Further research with a larger sample size and longer follow-up periods is essential to assess seasonal variations and enhance clinical guidelines for managing epistaxis in Iraq.